Comparing Exposure‐ and Coping Skills–Based Treatments on Trauma‐Related Guilt in Veterans With Co‐Occurring Alcohol Use and Posttraumatic Stress Disorders. Issue 4 (10th June 2020) - Capone, Christy; Tripp, Jessica C.; Trim, Ryan S.; Davis, Brittany C.; Haller, Moira; Norman, Sonya B.
Abstract: Posttraumatic stress disorder (PTSD) and substance use disorders (SUD) commonly co‐occur, and this comorbidity (PTSD–SUD) is associated with more severe symptoms and functional impairment than either disorder alone. Growing evidence indicates that trauma‐related guilt, typically concerning negative appraisals of one's actions or inaction during a traumatic event, is associated with PTSD, depression, suicidality, and, possibly, substance use. The present study examined whether integrated treatment for PTSD–SUD was effective in reducing trauma‐related guilt as measured by the Trauma‐Related Guilt Inventory. Data were drawn from a randomized clinical trial comparing the effectiveness of two integrated therapies on treatment outcomes in a sample of U.S. veterans ( N = 119) with comorbid PTSD and SUD. Participants were randomized to receive either Concurrent Treatment of PTSD and Substance Use Disorders Using Prolonged Exposure (COPE; n = 63) or Seeking Safety (SS; n = 56). The results indicated that global guilt decreased over time for the whole sample. However, there was a significant Treatment × Time interaction, such that participants in the COPE condition reported lower rates of global guilt, d = 0.940, over time compared to those in the SS condition, d = .498. To our knowledge, this was the first study to examine the effects of integrated PTSD–SUD treatment on trauma‐related guilt. The findings highlight that exposure‐based, trauma‐focused treatment for comorbid PTSD–SUD can be more effective in decreasing trauma‐related guilt, with potentially longer‐lasting effects, than non–exposure‐based treatment, adding evidence that patients with PTSD–SUD should be offered such treatment. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Comparando Tratamientos Basados en Exposición y en Estrategias de Afrontamiento para la Culpa Relacionada con el Trauma en Veteranos con Trastornos de Estrés Postraumático y por Consumo de Alcohol Concurrentes TERAPIA DE EXPOSICIÓN VS. HABILIDADES DE AFRONTAMIENTO DE TEPT‐SUD El trastorno de estrés postraumático (TEPT) y los trastornos por uso de sustancias (SUD en su sigla en inglés) comúnmente coexisten, y esta comorbilidad (TEPT‐SUD) se asocia con más síntomas graves y deterioro funcional que cualquiera de estos trastornos por sí solo. La creciente evidencia indica que la culpa relacionada con el trauma, típicamente en relación a evaluaciones negativas de las acciones o la no‐acción de uno durante un evento traumático, se asocia con TEPT, depresión, suicidalidad y, posiblemente, uso de sustancias. El presente estudio examinó si el tratamiento integrado para el TEPT‐SUD es eficaz para reducir la culpa relacionada con el trauma, medida con el Inventario de Culpabilidad Relacionada con el Trauma. Los datos se extrajeron de un ensayo clínico que compara la efectividad de dos terapias integradas en los resultados de tratamiento en una muestra de veteranos de Estados Unidos ( N = 119) con TEPT y SUD comórbidos. Los participantes fueron asignados al azar para recibir Tratamiento Concurrente de Trastorno de Estrés Postraumático y Trastornos por Uso de Sustancias usando Exposición Prolongada (COPE en su sigla en inglés; n = 63) o Buscando Seguridad (SS en su sigla en inglés; n = 56). Los resultados indicaron que la culpa global disminuyó con el tiempo para toda la muestra. Sin embargo, hubo una interacción significativa Tratamiento x Tiempo, de modo que los participantes en la condición COPE reportaron tasas más bajas de culpa global, d = 0.940, a través del tiempo, en comparación con aquellos en la condición SS, d = .498. Hasta donde sabemos, éste fue el primer estudio que examina los efectos del tratamiento integrado de TEPT‐SUD sobre la culpa relacionada con el trauma. Los hallazgos destacan que el tratamiento basado en la exposición y centrado en el trauma para el TEPT‐SUD comórbidos puede ser más eficaz para disminuir la culpa relacionada con el trauma, con efectos potencialmente más duraderos, que el tratamiento no basado en la exposición, añadiendo evidencia de que se les debería ofrecer tal tratamiento a los pacientes con TEPT‐SUD. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Comparing Exposure‐ and Coping Skills–Based Treatments on Trauma‐Related Guilt in Veterans with Co‐Occurring Alcohol Use and Posttraumatic Stress Disorders Traditional Chinese 標題: 患酗酒及創傷後壓力症共病的退役軍人中, 暴露為本及適應技巧為本的療法對創傷相關的內疚感的療效比較 撮要: 創傷後壓力症(PTSD)與藥物濫用失常(SUD)同時發生乃普遍情況, 而這種共病(PTSD–SUD)除了包含兩種疾病的症狀外, 亦跟更嚴重的症狀及功能受損有關。現在有越來越多證據顯示, 創傷相關的內疚感, 尤其是有關對個人行為的負面評價或在創傷事件中不作為的內疚感, 跟PTSD、抑鬱症、自殺傾向都相關, 亦很可能跟濫用藥物相關。本研究檢視PTSD–SUD的綜合治療, 對於減輕創傷相關的內疚感是否有效。我們採用創傷相關的內疚感量表來作測量。數據來自一個比較兩種綜合療法療效的隨機臨床試驗。樣本為患有PTSD與SUD共病的美國退役軍人 (N =119)。樣本被隨機分配接受兩者其一的PTSD與SUD並行治療:延長暴露療法 (COPE; n = 63), 或尋求安全治療 (SS; n = 56)。結果反映, 所有樣本整體的內疚感都隨時間減輕。但是, 當中反映有顯著的治療x時間交互作用, 即接受COPE的樣本)d = 0.940(相比接受SS的樣本)d = .498(, 其整體的內疚感隨時間發展水平亦較低。這是我們所知首個研究, 檢視PTSD–SUD的綜合治療對創傷相關的內疚感的效應。結果凸顯, 為PTSD–SUD的患者提供的暴露為本及聚焦創傷的治療, 相比非暴露為本的療法, 可以更有效地減輕創傷相關的內疚感, 及潛在可產生更持久的功效。此研究提供額外證據, 反映PTSD–SUD的患者應有這種治療選擇。 Simplified Chinese 标题: 患酗酒及创伤后压力症共病的退役军人中, 暴露为本及适应技巧为本的疗法对创伤相关的内疚感的疗效比较 撮要: 创伤后压力症(PTSD)与药物滥用失常(SUD)同时发生乃普遍情况, 而这种共病(PTSD–SUD)除了包含两种疾病的症状外, 亦跟更严重的症状及功能受损有关。现在有越来越多证据显示, 创伤相关的内疚感, 尤其是有关对个人行为的负面评价或在创伤事件中不作为的内疚感, 跟PTSD、抑郁症、自杀倾向都相关, 亦很可能跟滥用药物相关。本研究检视PTSD–SUD的综合治疗, 对于减轻创伤相关的内疚感是否有效。我们采用创伤相关的内疚感量表来作测量。数据来自一个比较两种综合疗法疗效的随机临床试验。样本为患有PTSD与SUD共病的美国退役军人 (N =119)。样本被随机分配接受两者其一的PTSD与SUD并行治疗:延长暴露疗法 (COPE; n = 63), 或寻求安全治疗 (SS; n = 56)。结果反映, 所有样本整体的内疚感都随时间减轻。但是, 当中反映有显著的治疗x时间交互作用, 即接受COPE的样本)d = 0.940(相比接受SS的样本)d = .498(, 其整体的内疚感随时间发展水平亦较低。这是我们所知首个研究, 检视PTSD–SUD的综合治疗对创伤相关的内疚感的效应。结果凸显, 为PTSD–SUD的患者提供的暴露为本及聚焦创伤的治疗, 相比非暴露为本的疗法, 可以更有效地减轻创伤相关的内疚感, 及潜在可产生更持久的功效。此研究提供额外证据, 反映PTSD–SUD的患者应有这种治疗选择。